Detstvo i yunost' Engel'sa. Put' k materializmu i kommunizmu. 1820-1844 gg.
Black and white photographs and paintings of Engels' early life Original title: Детство и юность Энгельса. Путь к материализму и коммунизму. 1820-1844 гг. PO-0605